Assessment of anti SARS-CoV-2 antibodies present in convalescent plasma donors aimed at being used in COVID-19 treatment (One Health & Risk Management, 2021)
Introduction. Currently, COVID-19 treatment includes several options, including the use of convalescent plasma. Therefore, the presence of anti-SARS-CoV-2 in blood donors after the clinical recovery of COVID-19, depending on their place of residence, age and the clinical manifestation of the disease is of scientific-practical interest.Material and methods. A total of 119 donors among patients were examined, namely males aged 18-60 years, having a past history of COVID-19 disease, being confirmed by PCR and treated, showing a negative PCR-based test result, which was performed at least 14 days after clinical recovery. The presence/absence of anti-SARS-CoV-2 was assessed by enzyme-linked immunosorbent assay.Results. The obtained data showed that 87.4% of plasma donors responded to COVID-19 infection by anti-SARS-CoV-2 IgG expression, being predominantly found in the 26-35 age group. Most donors experienced mild and medium clinical forms. It is important to note that all severe clinical manifestations of the infection were followed by formation of anti-SARS-CoV-2 IgG. Urban living environment was predominantly found in convalescent donors (75.0%), which indicates that they are better informed by medical institutions.Conclusions. The study shows that male blood donors aged 18-60 years, subsequently cured and being positive to anti-SARS-CoV-2 IgG can serve as a source of fresh plasma used for the treatment of COVID-19 patients.
Keywords: COVID-19 treatment; plasma donors; anti SARS-CoV-2; IgG class antibodies.